Al-Ghazālī on Reason, Legal, and Sufism: Toward an Integrative Epistemology of Islamic Law in Modernity - Akmal Bashori; Mutho'am; Muhammad Landung Hidayat (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This article examines the reconstruction of al-Ghazālī’s integrative epistemology of Islamic law through qualitative library research, using Iḥyā’ ‘Ulūm al-Dīn as the primary text and employing the analytical framework of bayānī, burhānī, and ‘irfānī epistemologies. The study reveals that al-Ghazālī consistently integrates Sufi ethics and burhānī logic into the discourse of fiqh, uncovering the inner meanings behind the formal structures of law. The synergy between bayānī reasoning (scriptural-normative), burhānī reasoning (rational-philosophical), and ‘irfānī reasoning (mystical-intuitive) produces an integral epistemological construction of fiqh in which law is inseparable from moral and spiritual dimensions, forming a unified and integrative epistemic system. This article further proposes a reconstruction of modern Islamic legal epistemology through three major agendas: the transformation of bayānī into maqāṣid-oriented ethical guidance, the emancipation of burhānī through critical engagement with modernity, and the humanization of ‘irfānī as a transformative spiritual ethic. Such an integrative epistemology enables fiqh to move beyond rigid legalistic dogma and emerge as a liberating and humanistic spirit of Islamic law.